Monitoring the software bug‐fixing process through the process mining approach. Issue 7 (27th March 2019) - Özdağoğlu, Güzin; Kavuncubaşı, Ece
Abstract: In the era of information technology, businesses have changed the way they work. Operations, which have become digitalized and managed via software systems, have increased in competitiveness. Software developers have been forced to design and implement their quality standards products by focusing on process‐oriented management. Software quality aims to gain a high‐performance level in the both development and managerial processes to maintain continuous improvements. Continuous improvements require more efficient process monitoring methods. Process mining, which provides recent techniques related to process monitoring, can be utilized with event log files to track the process performance. This research will extract the process mapping and performance statistics of the bug‐fixing process from event logs to develop an efficient process monitoring system. This process will uncover bottlenecks causing inefficiencies and risks. The benefits of process mining techniques will also be discussed to highlight the implications. In this context, this article will present a case study on monitoring the bug‐fixing process of a software product via process mining. It will reveal significant knowledge about subsequent steps and roles. Abstract : This paper presents a research on the bug‐fixing process of a software that reveals a significant knowledge about the details of the process. The main objective of this study is to discover bottlenecks of software bug life cycle process modeling with inefficiences, deviations, and risks via process mining as well as to extract real process mapping. The benefits of the process mining techniques are also discussed with various findings.